Policing in the Age of the Asylum: Early Legislative Interventions in the Lives of Persons with Disabilities - McNamara, Donna (Disability Studies Quarterly, 2021)
This article will trace the key legislative interventions in the lives of persons with disabilities in Ireland. It will explore the growth of a vast network of institutions and the subsequent legislative powers which were introduced to allow for the removal of persons deemed "dangerous" or "mad" from society. In particular, it will consider the powers afforded to police officers during both the age of institutionalisation and the age of deinstitutionalisation in the late twentieth century. It will be argued that the police have played a historically important role in the control and confinement of deviant persons, yet little is known about the extent to which they were involved in the removal of individuals to institutions such as asylums and workhouses. The police continue to play an integral role in the contemporary mental health system and this article will question whether this is appropriate especially in light of Ireland's ratification of the UN Convention on the Rights of Persons with Disabilities.